A reflection on integrated multi-disciplinary course in built environment - Abdullah, Fadzidah (2011)
The traditionally accepted way of working in the design studio in architectural education does not always address collaborative efforts required by the architectural profession. In fact, architectural education encourages the “primacy of the autonomous designer by focusing all its attention on the student’s experience as an individual” (Cuff, 1991). This phenomenon is unlike the real situation in an architectural practice environment, where architects collaborate with structural, electrical and mechanical consultants, landscape and interior designers, contractors, clients, end-users etc.The need to instill collaborative capability among architectural students is essential because the success of architects is dependent upon the application of knowledge from multiple disciplines.